Subsurface aeration alters the fungal composition of rhizosphere soil and tomato plant performance in Northwest China - Li, Yuan; Zhang, Mingzhi; Cao, Xiaoshu; Wang, Jingwei; Zhang, Zhenxing; Niu, Wenquan (International Journal of Agricultural and Biological Engineering, 2023)
Rhizosphere hypoxia constrains plant growth, and numerous studies have shown that root zone aeration accelerates plant photosynthesis and growth and increases crop yields. Nevertheless, the mechanism by which soil microorganisms are involved in this process is not clear. The purpose of the present study was to examine the effects of aeration and irrigation depth on the composition and structure of rhizosphere soil fungal communities and tomato plant performance. The amount of aeration assayed was equal to 0 (CK), 0.5 (V1), 1 (V2), and 1.5 (V3) times the porosity of the soil. The two depths of subsurface drip irrigation used were 15 (D15) and 40 cm (D40). The results demonstrated that soil aeration not only increased tomato plant performance but also influenced fungal diversity and composition. Compared to the no-aeration treatment, the V3 soil aeration treatment increased the total dry weight and fruit yield by 39.9% and 65.6%, respectively. The results also showed that the abundance of the phylum Ascomycota and the family Lasiosphaeriaceae increased with increasing soil aeration, whereas those of members of the phylum Zygomycota and the order Capnodiales decreased with increasing soil aeration. Moreover, the variation in subsurface irrigation depth altered the rhizosphere soil fungal community. In general, the results of this study demonstrate that root zone aeration can ameliorate hypoxic conditions in Lou soils and is beneficial to soil fungal communities and tomato plant performance. Keywords: tomato, soil aeration, rhizosphere soil fungal community, plant performance DOI: 10.25165/j.ijabe.20231601.6368 Citation: Li Y, Zhang M Z, Cao X S, Wang J W, Zhang Z X, Niu W Q. Subsurface aeration alters the fungal composition of rhizosphere soil and tomato plant performance in Northwest China. Int J Agric & Biol Eng, 2023; 16(1): 172–183.